Alternative generation of the output voltage waveform in an asymmetric transformer-based cascaded multilevel inverter under fault conditions (2022)
This paper introduces a method for the reconfiguration of a transformer-based cascaded multilevel inverter (CT-MLI), which allows the use of alternative switching patterns when individual inverter stages cease to operate as a result of a failure in the circuit switches. Different possibilities of reconfiguration of the inverter stages to provide the output voltage signal are analyzed and optimal switching patterns are determined. The results obtained from the simulation in the PSIM software are provided to validate the proposal